Infrared Drying as a Quick Preparation Method for Dried Tangerine Peel - Mingyue Xu; Guifang Tian; Chengying Zhao; Aftab Ahmad; Huijuan Zhang; Jinfeng Bi; Hang Xiao; Jinkai Zheng (International Journal of Analytical Chemistry)
To establish the most convenient and effective method to dry tangerine peels, different methods (sun drying, hot-air drying, freeze drying, vacuum drying, and medium- and short-wave infrared drying) were exploited. Our results indicated that medium- and short-wave infrared drying was the best method to preserve nutraceutical components; for example, vitamin C was raised to 6.77 mg/g (D.W.) from 3.39 mg/g (sun drying). Moreover, the drying time can be shortened above 96% compared with sun drying. Importantly, the efficiency of DPPH radical scavenging was enhanced from 26.66% to 55.92%. These findings would provide a reliable and time-saving methodology to produce high-quality dried tangerine peels.